New Evidence for the Dating of Cleitarchus (POxy LXXI.4808)? - Prandi, Luisa (Histos, 2012)
The recently published POxy LXXI. 4808, an evaluation of Alexander and Diadoch historians, says that Cleitarchus was the tutor of Ptolemy IV (Philopator), a notice that, if true, would significantly affect the ‘high’ dating of Cleitarchus by which he is assigned to the end of the 4th/beginning of the 3rd century BC. The present article re-assesses the evidence for the high dating of Cleitarchus, concluding that it remains likeliest, and that the new papyrus’ date is incorrect and ought not to affect the communis opinio.